Non-Contact Intracardiac Potential Mapping Using Mesh-Based and Meshless Inverse Solvers - Meng, Shu; Chamorro-Servent, Judit; Sunderland, Nicholas; Zhao, Jichao; Bear, Laura R.; Lever, Nigel A.; Sands, Gregory B.; LeGrice, Ian J.; Gillis, Anne M.; Budgett, David M.; Smaill, Bruce H. (Frontiers in Physiology, 2022)
Atrial fibrillation (AF) is the most common cardiac dysrhythmia and percutaneous catheter ablation is widely used to treat it. Panoramic mapping with multi-electrode catheters has been used to identify ablation targets in persistent AF but is limited by poor contact and inadequate coverage of the left atrial cavity. In this paper, we investigate the accuracy with which atrial endocardial surface potentials can be reconstructed from electrograms recorded with noncontact catheters. An in-silico approach was employed in which “ground-truth” surface potentials from experimental contact mapping studies and computer models were compared with inverse potential maps constructed by sampling the corresponding intracardiac field using virtual basket catheters. We demonstrate that it is possible to 1) specify the mixed boundary conditions required for mesh-based formulations of the potential inverse problem fully, and 2) reconstruct accurate inverse potential maps from recordings made with appropriately designed catheters. Accuracy improved when catheter dimensions were increased but was relatively stable when the catheter occupied >30% of atrial cavity volume. Independent of this, the capacity of noncontact catheters to resolve the complex atrial potential fields seen in reentrant atrial arrhythmia depended on the spatial distribution of electrodes on the surface bounding the catheter. Finally, we have shown that reliable inverse potential mapping is possible in near real-time with meshless methods that use the Method of Fundamental Solutions.